EFL Teachers’ Perceptions Towards the Implementation of Online Formative Assessment Amidst the Covid-19 Pandemic - Fitri Rahmawati Astiandani; Syafi'ul Anam (ELT Worldwide: Journal of English Language Teaching, 2021)
During the pandemic era, the educational system has made several adaptations, including the ways of assessing students. One type of assessment that teachers frequently use is formative assessment. A large number of online platforms can be used as formative assessment tools at this time. Thus, this study explores the EFL teachers’ perceptions of their implementation of online formative assessment, its affordances and constraints during its implementation, as well as ways to overcome constraints. A qualitative research design is employed in this study. Data was gained from six Indonesian secondary EFL teachers through an open-ended questionnaire. Findings revealed the same perceptions of both groups, namely positive. Even though teachers are from public or private schools, they experience the same affordances and constraints when implementing online formative assessment. Moreover, they also shared several ways to deal with the constraints and conveyed their suggestions to the stakeholders in the educational sector. The findings of this study will encourage educational stakeholders, especially teachers, to enhance the quality of the education system by ameliorating the assessment aspects in the teaching and learning process.